One-time fertilization of controlled-release urea with compound fertilizer and rapeseed cake maintains rice grain yield and improves nitrogen use efficiency under reduced nitrogen conditions - Hu, Yajie; Cai, Qin; Xu, Yi; Xue, Jiantao; Yu, Enwei; Wei, Haiyan; Xu, Ke; Huo, Zhongyang; Zhang, Hongcheng (Frontiers in Plant Science, 2023)
Nitrogen (N) rate reduction and simplified fertilization can mitigate environmental impacts and reduce the involvement of manual labor in rice (Oryza sativa L.) production. Controlled-release urea (CRU) has been recommended as an effective alternative technique to conventional urea fertilization, and it can improve rice yield and N use efficiency (NUE) and reduce labor costs.However, the information on the effects of one-time fertilization with CRU on maintaining yield and improving NUE under reduced chemical N conditions is limited. In this study, controlled-release bulk blending fertilizer (CRF), consisting of CRU with release periods of 40 and 100 days, mixed with compound fertilizer, was applied as basal fertilizer. Increased ~20% plant density (ID) and rapeseed cake fertilizer (RC, increase 20% organic N) were combined with CRF, respectively. The N treatments with 20% chemical N reduction were as follows: reduced N fertilizer (RNF), CRF, CRF+ID, and CRF+RC. In addition, a conventional split fertilizer application with 300 kg ha -1 N was applied as the control (CK). Rice yield and its components, dry matter accumulation, N uptake, and NUE were investigated to evaluate whether one-time N fertilization realized stable yield and high NUE under reduced 20% chemical N conditions.Compared with CK, the CRF+RC treatment exhibited a comparable grain yield, while the other reduced N treatments (RNF, CRF, and CRF+ID) had a lower grain yield. Moreover, CRF+ID exhibited a higher rice grain yield than RNF or CRF under the same N level. Irrespective of exogenous organic N, CRF+RC exhibited significantly higher NUE than CK. The CRF+ID treatment showed a significantly higher N partial factor productivity (PFN) than CK but comparable N agronomic efficiency (NAE) and N recovery efficiency (NRE). Therefore, a one-time fertilizer application of CRF+RC maintained grain yield and improved the NUE while reducing the N rate and fertilization times, demonstrating its potential application in rice production.